Advances in civil engineering and building materials : selected, peer reviewed papers from 2nd International Conference on Civil Engineering and Building Materials(CEBM 2012), 17-18 November 2012, Hong Kong - International Conference on Civil Engineering and Building Materials(CEBM 2012) (2nd : 2012 : Hong Kong); Chang, Shuenn-Yih; Al-Bahar, Suad Khalid; Zhao, Jingying (London : CRC, 2012)
Includes bibliographical references and index